2019
DOI: 10.21037/jtd.2019.01.31
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrence in stage I adenocarcinoma of the lung: a multi-institutional study on synergism between type of surgery and type of nodal staging

Abstract: Background: In last years, an increasing interest emerges on the role of sub-lobar resection and lobespecific lymph nodal dissection in the treatment of early-stage lung cancer. The aim of our study was to define the impact on cumulative incidence of recurrence (CIR) of type of surgical resection and type of nodal staging in this subset of patients. Furthermore, we evaluated the possible synergism between the different kinds of procedure. Methods: An analysis of 969 consecutive stage I pulmonary adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Nevertheless, some studies have reported a remarkable FN rate in invasive lung adenocarcinoma, compared to other histological types such as squamous cell carcinoma, adenosquamous carcinoma, and large-cell carcinoma [8]. For this reason, we focused on invasive lung adenocarcinoma only, and our results indicate a not inconsiderable risk of FN findings in this context [12,25].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, some studies have reported a remarkable FN rate in invasive lung adenocarcinoma, compared to other histological types such as squamous cell carcinoma, adenosquamous carcinoma, and large-cell carcinoma [8]. For this reason, we focused on invasive lung adenocarcinoma only, and our results indicate a not inconsiderable risk of FN findings in this context [12,25].…”
Section: Discussionmentioning
confidence: 79%
“…In recent years, there has been a growing awareness of the clinical implications of the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society/American Thoracic Society/European Respiratory Society (IASLC/ATS/ERS) histopathological classification of lung adenocarcinomas [9]. Several studies have evaluated the association between IASLC/ATS/ERS patterns and clinical characteristics, tumour features, cells of origin, mutational profile, and prognosis [10][11][12][13][14]. Nevertheless, only a few studies have tried to find a correlation between IASLC/ATS/ERS histopathological pattern and FDG-PET findings [15].…”
Section: Introductionmentioning
confidence: 99%
“…Last year, an article reported the cumulative incidence of recurrence (CIR) between LND and SND. 28) And the result showed a significantly higher CIR in LND group. Another study reported that even in clinical stage Ia patients, mediastinal lymph node metastases or beyond lobe-specific zone were sometimes found.…”
Section: Discussionmentioning
confidence: 86%
“…Among stage I adenocarcinomas, multiinstitution studies have observed a 26% recurrence rate after complete surgical resection. 5 Therefore, it is clear that some patients retain micrometastatic disease after complete resection of early-stage lung cancer. Systemic therapy improves survival in patients with micrometastatic disease.…”
Section: The Assumptions Of Adjuvant Therapy In Early-stage Lung Cancermentioning
confidence: 99%